The Challenges of Interpreting Multilingual, Multijural Legislation Symposium: Creating and Interpreting Law in a Multilingual Environment: Panel I: National Law in a Multilingual Society - The Canadian Exerience - Sullivan, Ruth (Brooklyn Journal of International Law, 2003)
Disclaimer: This summary was generated by AI based on the content of the source document.